ClinGen advancing genomic data‐sharing standards as a GA4GH driver project. Issue 11 (11th October 2018) - Dolman, Lena; Page, Angela; Babb, Lawrence; Freimuth, Robert R.; Arachchi, Harindra; Bizon, Chris; Brush, Matthew; Fiume, Marc; Haendel, Melissa; Hansen, David P.; Milosavljevic, Aleksandar; Patel, Ronak Y.; et al.
Abstract: The Clinical Genome Resource (ClinGen)'s work to develop a knowledge base to support the understanding of genes and variants for use in precision medicine and research depends on robust, broadly applicable, and adaptable technical standards for sharing data and information. To forward this goal, ClinGen has joined with the Global Alliance for Genomics and Health (GA4GH) to support the development of open, freely‐available technical standards and regulatory frameworks for secure and responsible sharing of genomic and health‐related data. In its capacity as one of the 15 inaugural GA4GH "Driver Projects, " ClinGen is providing input on the key standards needs of the global genomics community, and has committed to participate on GA4GH Work Streams to support the development of: (1) a standard model for computer‐readable variant representation; (2) a data model for linking variant data to annotations; (3) a specification to enable sharing of genomic variant knowledge and associated clinical interpretations; and (4) a set of best practices for use of phenotype and disease ontologies. ClinGen's participation as a GA4GH Driver Project will provide a robust environment to test drive emerging genomic knowledge sharing standards and prove their utility among the community, while accelerating the construction of the ClinGen evidence base. Abstract : The Clinical Genome Resource (ClinGen) has joined with the Global Alliance for Genomics and Health (GA4GH) to support the development of open, freely‐available technical standards and regulatory frameworks for secure and responsible sharing of genomic and health‐related data. In its capacity as one of the 15 inaugural GA4GH "Driver Projects, " ClinGen is providing input on the key standards needs of the global genomics community, and has committed to participate on GA4GH Work Streams to help develop and test drive GA4GH deliverables.